3(6-x)=27/6-6

Simple and best practice solution for 3(6-x)=27/6-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(6-x)=27/6-6 equation:


x in (-oo:+oo)

3*(6-x) = 27/6-6 // - 27/6-6

3*(6-x)-(27/6)+6 = 0

3*(6-x)-9/2+6 = 0

(2*3*(6-x))/2-9/2+(2*6)/2 = 0

2*3*(6-x)+2*6-9 = 0

12-6*x+27 = 0

39-6*x = 0

(39-6*x)/2 = 0

(39-6*x)/2 = 0 // * 2

39-6*x = 0

39-6*x = 0 // - 39

-6*x = -39 // : -6

x = -39/(-6)

x = 13/2

x = 13/2

See similar equations:

| (x-5)(4x-3)=(1-3x)(x+1) | | 8/1.3*100/x | | (x-6)(3x-2)=(2x-3)(x-10) | | (x+3)(x-5)=(x+3)(x+3) | | (x+3)(x-5)=(x+3)x(x+3) | | 0.4a+0.7(13-a)=7.6 | | 9=-9b+2b | | 2x-35=2x+9 | | 9n-36=-18 | | 4(x-3)=12(x-5) | | p-9=-6p-3 | | 2x+20+4x-10=180 | | 3(x+4)-4=3(x-4) | | 0.25y=12 | | 3(x-4)-4=3(x-4) | | lnx=22.87 | | 2.5(fk+2)=12k | | 4x+3x=182 | | y^6-3y^4-y^3+3y^2-1=0 | | -6(6x-1)=-36x-6 | | 144x^2-1/4=0 | | y-9=-1(x-16) | | 50-2x=15+3x | | 14(v+4)-2v=3(4v+4)-18 | | y-9=-0.66(x-16) | | y-9=-(2)/(3)(x-16) | | y-9=-2/3(x-16) | | 3x-208=x/9 | | 5(x+7)=-30(x+2) | | -5(x+4)+3x+5=5x+12 | | -7(x+3)+3x+7=5x+11 | | ((d-4)/(4))^(2)=64 |

Equations solver categories